2011
DOI: 10.1111/j.1540-8175.2011.01443.x
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Measurement of Circumferential Carotid Arterial Strain by Two-Dimensional Speckle Tracking Imaging in Healthy Subjects

Abstract: 2DS in the CCAs is simply and quickly performed with high feasibility and excellent reproducibility. In healthy subjects, age and pulse pressure are the most important determinants of mean CAS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
43
1
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(53 citation statements)
references
References 20 publications
(54 reference statements)
7
43
1
2
Order By: Relevance
“…But it might not directly affect the results given that a previous study conducted on healthy subjects showed that segmental variation in CCA CirS was not significant. 32 Second, hemodynamic deterioration during grafting may also be a consequence of regional ischemia imposed by transient coronary hemostasis, which could confound the observed results. The influence of ischemic insult on the degree of hemodynamic deterioration, however, is usually subclinical and difficult to assess separately.…”
Section: Discussionmentioning
confidence: 82%
“…But it might not directly affect the results given that a previous study conducted on healthy subjects showed that segmental variation in CCA CirS was not significant. 32 Second, hemodynamic deterioration during grafting may also be a consequence of regional ischemia imposed by transient coronary hemostasis, which could confound the observed results. The influence of ischemic insult on the degree of hemodynamic deterioration, however, is usually subclinical and difficult to assess separately.…”
Section: Discussionmentioning
confidence: 82%
“…In agreement with previous studies,15, 16 CAAS measurement using 2D‐ST echocardiography in the present study demonstrated the heterogeneous motion pattern and local variations in compliance of different segments of the ascending aortic wall (Figure 1B and 1C). According to previous investigators,14, 15 we divided the ascending aortic wall into 6 equally sized segments. A global CAAS was calculated as the mean value of peak CAAS of the 6 segments.…”
Section: Discussionmentioning
confidence: 99%
“…A global circumferential ascending aortic strain (CAAS) was calculated as the mean value of peak CAAS of the 6 segments. A corrected CAAS was calculated as the global CAAS/pulse pressure, according to Yuda et al 14. A global radial ascending aortic strain (RAAS) was calculated as the mean value of peak RAAS of the 6 segments.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The initial systolic frame generally served as the frame of interest, to include maximal aortic wall expansion and recoil. As in other instances [10,22], aortic wall was divided into six equidistant regions, all similar in size. In each region, numeric expressions of each 2D-ST variable represented mean values calculated from all points in arterial segments.…”
Section: Two-dimensional Speckle-tracking Strain Echocardiographymentioning
confidence: 99%